2020
DOI: 10.1371/journal.pone.0236712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the implementation of the Reproductive Life Plan in disadvantaged communities: A mixed-methods study using the i-PARIHS framework

Abstract: Introduction The Reproductive Life Plan (RLP) is a clinical tool to help clients find strategies to achieve their reproductive goals. Despite much research on the RLP from high-income countries, it has never been studied in low-or middle income countries. Together with health workers called Mentor Mothers (MMs), we used a context-adapted RLP in disadvantaged areas in Eswatini. Our aim was to evaluate the implementation of the RLP in this setting. Methodology MMs participated in focus group discussions (FGDs, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“… Sandstrom et al (2015) [ 17 ] a Geerligs et al (2020) [ 19 ] a Societal culture, social systems, or hegemony Note. Particularly relevant in implementation of public health interventions Niemeyer Hultstrand et al (2020) [ 18 ] b Conceptualization of leadership Leadership as a social collective process that has dynamic relationships with team culture, is characterized by diversified styles and diverse actions and operates in multiple ways and on multiple levels in the organization. Oye et al (2016) [ 23 ] a Leadership (of nurse managers) as a facilitator of evidence implementation: • Effective teamwork ○ Communication between managers and staff nurses ○ Foster collaboration • Effective organizational structures ○ Strategic governance (leadership combining management and clinical experience, awareness of the impact of improved outcomes) • Transformational leadership ○ Influence on evidence application (culture of expectations, inspiring a shared vision, sustaining evidence-based practice) ○ Readiness for change among leaders (enabling empowering, focus on teaching and learning, recognition, using resources in management) Note.…”
Section: Resultsmentioning
confidence: 99%
“… Sandstrom et al (2015) [ 17 ] a Geerligs et al (2020) [ 19 ] a Societal culture, social systems, or hegemony Note. Particularly relevant in implementation of public health interventions Niemeyer Hultstrand et al (2020) [ 18 ] b Conceptualization of leadership Leadership as a social collective process that has dynamic relationships with team culture, is characterized by diversified styles and diverse actions and operates in multiple ways and on multiple levels in the organization. Oye et al (2016) [ 23 ] a Leadership (of nurse managers) as a facilitator of evidence implementation: • Effective teamwork ○ Communication between managers and staff nurses ○ Foster collaboration • Effective organizational structures ○ Strategic governance (leadership combining management and clinical experience, awareness of the impact of improved outcomes) • Transformational leadership ○ Influence on evidence application (culture of expectations, inspiring a shared vision, sustaining evidence-based practice) ○ Readiness for change among leaders (enabling empowering, focus on teaching and learning, recognition, using resources in management) Note.…”
Section: Resultsmentioning
confidence: 99%
“…This also influenced the participants’ experiences of how appropriate it was to use the KROSS tool in their services. Integration in the services’ existing routines and systems [ 31 ], together with a motivation for gaining additional knowledge and better routines for vision after stroke, were the facilitators for a sustainable change of practise [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other individual studies have also shown that RLP is feasible in both HIC and LMICs. 44 45 While the aforementioned studies indicate that RLP interventions are acceptable and feasible to health providers and patients, more research is required to explore potential benefits in adolescent populations, specifically.…”
Section: Discussionmentioning
confidence: 99%
“…One study of a modified RLP intervention delivered to adult women in Eswatini, South Africa, by community workers called Mentor Mothers reported increased knowledge and confidence to facilitate RLP conversations with women in the Mentor Mothers. 45 Whether more knowledgeable and confident Mentor Mothers increased women's knowledge or changed health behaviors was not explored, but there was reported increased contraception uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation